Analysis of the Behavior of Pregnant Women About the Importance of the Covid-19 Vaccine in the Work Area of the Regional Technical Implementation Unit (UPTD) of the Tirtajaya Health Center - Selpi Auliawati; Omega DR Tahun (Global Writing Academica Researching and Publishing, 2022)
According to WHO (2021) Indonesia itself has confirmed 4,066,404 cases, with 131,372 confirmed cases of death (Covid-19 Task Force, 2021). Vulnerable groups are at greater risk, one of which is pregnant women. Pregnant women with COVID-19 occur in the first, second and third trimesters. COVID-19 infection in pregnant women can affect the organs of genesis and fetal development. The earlier the case of infection, the greater the risk of miscarriage. Pregnant women with COVID-19 are more likely to give birth prematurely. Research Objectives is to find out the factors that influence the behavior of pregnant women carrying out the Covid 19 vaccine in the Working Area of ​​the Tirtajaya Health Center, Tirtajaya District, Karawang Regency in 2022. Analytical with cross sectional approach. The sample in this study were 76 pregnant women at the Tirtajaya Health Center in March-November 2022 (total sampling). The results of this study indicate that the factors that influence the behavior of pregnant women carrying out the Covid 19 vaccine are work factors (p value = 0.045), information factors (p value = 0.000), distance factors (p value = 0.032), education factors (p value = 0.015) with the behavior of the Covid-19 vaccine in pregnant women. Health centers are expected to hold education about the covid-19 vaccine through seminars and it is hoped that health workers will increase information around the puskesmas or posyandu such as posters, leaflets, banners related to the importance of the covid-19 vaccine in pregnant women.